2006
DOI: 10.1136/bmj.332.7537.358
|View full text |Cite
|
Sign up to set email alerts
|

Applying clinical epidemiological methods to health equity: the equity effectiveness loop

Abstract: Focusing on the average effects of interventions on health may miss important differences within populations. Examining these effects across gradients in wealth allows the identification of the interventions most likely to reduce health inequalities

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
147
0
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(157 citation statements)
references
References 0 publications
3
147
0
7
Order By: Relevance
“…It is crucial to determine whether there is a social deprivation dimension to any shortfall in service delivery so that the programme can be adjusted to address this issue. 11 More generally, the staggered roll-out of the programme complicates the interpretation and comparison of data across and within NHS Board areas. childsmile practice Figure 1 indicates the level of assessment and referral activity achieved within Childsmile Practice in the West of Scotland.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is crucial to determine whether there is a social deprivation dimension to any shortfall in service delivery so that the programme can be adjusted to address this issue. 11 More generally, the staggered roll-out of the programme complicates the interpretation and comparison of data across and within NHS Board areas. childsmile practice Figure 1 indicates the level of assessment and referral activity achieved within Childsmile Practice in the West of Scotland.…”
Section: Discussionmentioning
confidence: 99%
“…However, Table 2 shows the extent to which referral fails to result in a practice visit, and further analysis is underway to map the extent to which there may be a social deprivation aspect to this attrition. 11 The Childsmile Practice monitoring database, holding information on approximately 35,000 children derived from paper based proformas, is dependant on complete and accurate manual completion of forms by health visitors, Dental Health Support Workers, and practices. Evidence of inconsistencies between areas, including failure to record contacts outside the practice ie at the family home, has prompted the simplification of record keeping and explicit management guidance regarding what is to be recorded by practices, health visitors and Dental Health Support Workers.…”
Section: Discussionmentioning
confidence: 99%
“…9 Expanding on our recentlyt published equityteffectiveness loop ( Fig. 1) framework, 3 we propose an evidencet based framework -or "cascade" -for equitytoriented knowledge translation (Fig. 2), drawing on systematic reviews to assess barriers and facilitators, identifying interventions to overcome barriers, choosing appropriate KT strategies, evaluation, through to knowledge management and sharing.…”
Section: ‫صفحة‬ ‫يف‬ ‫بالعربية‬ ‫امللخص‬ ‫عىل‬ ‫االطالع‬ ‫ميكن‬mentioning
confidence: 99%
“…2 Furt t thermore, we have recently shown that the community effectiveness of intervent t tions is lower in the poorest populations owing to a "staircase" effect of lower covt t erage and/or access, inferior diagnostic accuracy, less provider compliance and less consumer adherence. 3 The WHO Knowledge Management and Sharing (KMS) group adapted the Canadian Institutes of Health Research definition of knowledge translation 4 (KT) for lowert and middletincome countries (LMIC) as: "the synthesis, exchange and application of knowledge by relevant stakeholders to accelerate the benefits of global and local innovation in strengthening health systems and improving people's health." 5 In addition to this focus on health systems, we .…”
Section: Introductionmentioning
confidence: 99%
“…The "community effectiveness" of a given technology, namely its impact when applied in a "real world" setting compared with the experimental environment of a clinical trial, may vary for different population groups as it takes into account contextual factors (6). Thus, to assess the real world consequences of adopting a given health technology, contextual elements need to be considered and the corresponding evidence sources and types included in evaluations (7)(8)(9)(10).…”
mentioning
confidence: 99%